The Pricing of IPO Services and Issues: Theory and Estimation - Kang, Ari; Lowery, Richard (The Review of Corporate Finance Studies, 2014)
We estimate a model for the process for setting IPO spreads and offer prices. We establish that the partially rigid spread schedule observed for IPOs, where over 90% of IPOs with proceeds between $20 and $80 million have a spread of 7%, can be rationalized as optimal collusion. Optimal collusion creates a rationale for high underpricing, and we use data on both spreads and underpricing to estimate structural parameters. Our estimates suggest that firms benefit from holding IPOs but that idiosyncratic manager preferences may drive much of the IPO market. Much of the money left on the table is estimated to accrue to underwriters.